Pengaruh Beban Berlebih Terhadap Rencana Umur Jalan (Studi Kasus Jalan Mayjen Sungkono Kota Malang) - Gatur, Fergilus; Rahma , Pamela Dinar; Arifianto , Andy Kristafi (Fakultas Teknik Universitas Tribhuwana Tunggadewi, 2023)
Land transportation infrastructure as referred to in Law No. 38/2004 includes all roads as well as equipment and supplies necessary for land, air and sea traffic; railways and cable cars are not included in this definition. With the increase in the number of transportation modes and traffic density, the functional quality and integrity of the road deteriorates. The two main causes of road surface deterioration are vehicle overloading and substandard road construction. The study aims to determine the level of overloading on the projected road life and the magnitude of the influence of excess vehicle traffic on the expected road life in order to determine the actual conditions on Mayjen Sungkono Road, Malang City. In this study, AASTHO and EASAL techniques were used. Based on the results of the study, on the peak day there was an overflow of vehicles on Mayjen Sungkono Road, Malang City as many as 44,938 vehicles and Mayjen Sungkono Road, Malang City as many as 9,090 vehicles. In addition, the estimated life of the road is shortened by 1.96 years, with the estimated life of the road ranging from 2023 to 2028.